Psoriasis, fracture risk and bone mineral density: the HUNT Study, Norway. (1st May 2017) - Modalsli, E.H.; Åsvold, B.O.; Romundstad, P.R.; Langhammer, A.; Hoff, M.; Forsmo, S.; Naldi, L.; Saunes, M.
Summary: Background: An association between psoriasis and osteoporosis has been reported. Objectives: To investigate, in a large prospective population‐based Norwegian study, whether psoriasis is associated with increased risk of forearm or hip fracture; to investigate the cross‐sectional association between psoriasis and bone mineral density (BMD) T‐score in a subpopulation. Methods: Hospital‐derived fracture data from Nord‐Trøndelag County (1995–2013) were linked to psoriasis information, BMD measurements and lifestyle factors from the third survey of the Nord‐Trøndelag Health Study 2006–08 (HUNT3); socioeconomic data from the National Education Database; and use of medication from the Norwegian Prescription Database. Results: Among 48 194 participants in HUNT3, we found no increased risk of forearm or hip fracture in 2804 patients with self‐reported psoriasis [overall age‐ and sex‐adjusted hazard ratio 1·03, 95% confidence interval (CI) 0·82–1·31]. No clear association was found between psoriasis and mean BMD T‐score; overall age‐ and sex‐adjusted differences in total hip, femoral neck and lumbar spine BMD T‐scores were 0·02 (95% CI −0·11 to 0·14), 0·05 (95% CI −0·06 to 0·17) and 0·07 (95% CI −0·09 to 0·24), respectively. No clear association was found between psoriasis and prevalent osteoporosis in either total hip, femoral neck or lumbar spine; overall age‐ and sex‐adjusted odds ratio was 0·77 (95% CI 0·54–1·10). Associations did not change substantially after adjustment for education, smoking, systemic steroid use and body mass index. Conclusions: We found no association between psoriasis and risk of fracture. The study did not indicate reduced BMD T‐score or higher prevalence of osteoporosis among patients with psoriasis.